2016
DOI: 10.1590/01047760201622042213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impregnation With Styrene and Nano-Zinc Oxide on Fire-Retarding, Physical, and Mechanical Properties of Poplar Wood

Abstract: Nanoparticles have been vastly applied in wood polymer composites (WPCs) in the recent years to improve some of the drawbacks of solid wood species. In the present study, the effects of ZnO nanoparticles on fire retarding, physical, and mechanical properties of polymerized poplar wood were investigated. Poplar specimens were impregnated with styrene monomer, containing four different contents of nanozinc oxide (ZnO) (0, 0.5, 1 and 1.5%, based on the dry weight of monomer). Results of the scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Produtos ignífugos ou retardadores de chama revestidos superficialmente, incorporados ou impregnados na madeira, formam uma camada protetora que evita a propagação superficial da chama ao se fundir com a elevação da temperatura, retarda o tempo de ignição e reduz a taxa de liberação de calor [1][2][3]6,7] Muitas pesquisas têm examinado a eficácia de retardadores de fogo, dentre eles: solução contendo uréia [8], boro [9], fósforo [10] e partículas inorgânicas [11], cada um com suas próprias vantagens e limitações em termos de eficácia, custos e impactos ambientais. Especialmente, a modificação com materiais inorgânicos em escala nanométrica é considerada promissora para aumentar a resistência da madeira ao fogo [1,12]. Dentre as estruturas nanométricas utilizadas para revestir a superfície da madeira, o TiO 2 têm sido investigado, pois acredita-se que os efeitos sinérgicos resultantes das interações com a matriz madeira, são capazes de proporcionar propriedades térmicas mais estáveis [1,11].…”
Section: Introductionunclassified
“…Produtos ignífugos ou retardadores de chama revestidos superficialmente, incorporados ou impregnados na madeira, formam uma camada protetora que evita a propagação superficial da chama ao se fundir com a elevação da temperatura, retarda o tempo de ignição e reduz a taxa de liberação de calor [1][2][3]6,7] Muitas pesquisas têm examinado a eficácia de retardadores de fogo, dentre eles: solução contendo uréia [8], boro [9], fósforo [10] e partículas inorgânicas [11], cada um com suas próprias vantagens e limitações em termos de eficácia, custos e impactos ambientais. Especialmente, a modificação com materiais inorgânicos em escala nanométrica é considerada promissora para aumentar a resistência da madeira ao fogo [1,12]. Dentre as estruturas nanométricas utilizadas para revestir a superfície da madeira, o TiO 2 têm sido investigado, pois acredita-se que os efeitos sinérgicos resultantes das interações com a matriz madeira, são capazes de proporcionar propriedades térmicas mais estáveis [1,11].…”
Section: Introductionunclassified
“…The results indicate that the treatment greatly improved the dimensional stability and reduced the hygroscopicity of the treated wood [12]. In addition, it was reported that the presence of ZnO NPs on the wood surface led to increased mechanical properties in comparison to control specimens [13,14]. In another study, it was reported that the presence of ZnO NPs on the surface of wood enhanced the hydrophobic properties and anti-UV photochromic properties [15].…”
Section: Introductionmentioning
confidence: 91%
“…Despite the low levels of FSNPs in wood (Table 1), ASE was high, ranging from 49.23% to 63.96%, depending on treatment type and wood species. Besides the improved hydrophobic character, this was attributed to the clogging effect of the nanoparticles by occupying void spaces in the wood tissue [46][47][48][49]. Overall, this results in the FSNP layers on the cell wall surfaces blocking water molecules from the bonding sites.…”
Section: Anti-swelling-efficiency (Ase) and Swelling Anisotropymentioning
confidence: 99%